Efektivitas Edukasi Media Booklet Pasien Diabetes Mellitus Tipe 2 Kualitas Hidup Rawat Jalan di RS Anwar Medika - Khurin In Wahyuni; Antonius Adji Prayitno Setiadi; Yosi Irawati Wibowo (Fakultas Farmasi Universitas Pancasila, 2020)
DM management is expected to improve the quality of life of patients because the quality of life is the ﬁ nal result of each medical intervention; therefore, it becomes a standard of every succesful therapy. One of the improvements in quality of life can be done through education. In providing education, booklet method can be an eﬀective way to deliver information about the activities problem. This study used one-group pre-test post-test design. This study aims to determine the quality of life before and after giving education to outpatients in Anwar Medika Hospital from November 2017 to January 2018 with sample of 109 patients. The measurement of quality of life improvement was measured by the Diabetes Quality of Life (DQOL) score which has 4 domains: satisfaction domain, the impact of DM concerns due to DM and physical, psychological and social concerns. Quantitative analysis carried out by the Wilcoxon signed rank test and showed that there are diﬀerences in quality of life with signiﬁcance of 0.000 (p <0.005) from each domain. Therefore, it can be concluded that, education could impact an important role on improving quality of life.